ORGANIZATIONAL COMMUNICATION ROLE OF ISLAMIC STUDENTS IN FORMING THE PERSONALITY OF THE KADER (Analysis Study Ordinary Members in HMI of the Agricultural Commissariat in Lampung University, Labuhan Ratu, Bandar Lampung) - dani setiawan; eny inti suryani (DEMOKRASI, 2021)
The background of this research is the communication process that exists in the organization of Islamic Student Association (HMI) which has not run optimally because students who are members of the HMI are pluralistic and have hedon, it develops with changes in times and there aret conflict with Islamic teachings themselves. Based on the background of the cadre, the HMI of the Unila Agricultural Commissariat has an important role in approaching its cadres. One of the approaches is the programm of the Kader I workshop which focuses on the formation of positive HMI cadres (Regular Members). The formulation of this research problem is: What is the Role of Organizational Communication of Islamic Student Associations in Forming Cadre Personality. The research method used descriptive qualitative. The author used the Snowball Sampling technique, where the research informants are selected based on the instructions of the Key Informant (Main Informant). Data collection techniques used were in-depth interviews (Indepth Interview), Observation and Literature Study. The data analysis technique used qualitative data analysis techniques. By using the AIDDA approach, the researcher can conclude that the role of the organizational communication of the Islamic Student Association of the Unila Agricultural Commission, which is intended to form a positive cadre personality, is less effective. Based on the results of interviews with the three informants, they stated that the communication patterns that occurred as well as cadre training had been carried out well, but the reality showed the values of hedonism. Keywords: Organizational Communication, Positive Cadre Personality